Nature inspiration, imitation, and emulation: Biomimicry thinking path to sustainability in the construction industry - Oguntona, Olusegun Aanuoluwapo; Aigbavboa, Clinton Ohis (Frontiers in Built Environment, 2023)
The construction industry has been globally fingered as the major sector responsible for the continued deplorable state of the environment. The rising exploitation of the natural environment by the sector decapacitates the function of the flora and fauna to sustain life on earth. Therefore, the adoption and implementation of sustainability concepts in the construction industry are imperative to reduce the sector’s negative impacts on the environment. The growing field of biomimicry as a sustainability concept has increased global interest and call to maximize the numerous benefits offered by nature. This article is aimed at exploring biomimicry potentials in solving human challenges in a sustainable manner through responsible imitation, emulation, and drawing inspiration from nature. The first part of this paper explores the construction industry with rapt attention to its positive and negative impact on the human and natural environment. The second part provides a comprehensive overview of the biomimicry concept looking at its definitions, tenets, and sustainability standpoint. Finally, biomimicry inspiration, imitation, and emulation are discussed citing examples of their applications within and outside the built environment.